Gambaran Tingkat Pengetahuan Ibu tentang Pertolongan Pertama Luka Bakar Anak Usia Toddler - Widi Antoro; Irma Mustika Sari (CV. Ulil Albab Corp, 2022)
The toddler age has a very strong curiosity to trace and experiment that is not balanced with the ability to understand something or react to danger, so toddler-age children are very susceptible to burn injury. The need for parental knowledge, especially mothers, towards first aid for burns in children, the level of maternal knowledge about handling burns in toddler-aged children is very necessary as an effort not to aggravate burns in toddler-age children. Objective to know an overview of the mother's level of knowledge about first aid for burns in toddler-age children in the work area of the kartasura health center. This type of research uses descriptive quantitative with a crosssectional approach method. Sampling using random sampling method with criteria and exclusion, population of 492 mothers, sample of 83 respondents. The results of statistical tests on respondents showed that 75 respondents (90.4%) were good, the category was sufficient 8 (9.6%), the category was less than 0 respondents (0%). The results of the study showed that the level of maternal knowledge of first aid in burns of toddler-aged children in the work area of the kartasura health center was in a good category)